Вербальна реалізація міжкультурної комунікації у перекладі - Врабель Томаш; Vrábely Tamás; Tomash Vrabel (Поліграфцентр "Ліра", 2011)
Резюме. Стаття присвячена дослідженню способів вираження міжкультурноїl комунікації у перекладі. Розглядаються види й визначення перекладу, компоненти комунікативної компетенції та способи адекватної передачі міжкультурної комунікації у перекладі. Автор доходить ви сновку, що міжкультурна компетенція спеціаліста, який володіє інозе¬мною мовою й основними навичками перекладу, співвідноситься з його комунікативною компетенцією, додає їй міжкультурний вимір, при цьому має власні компоненти, які не входять у комунікативну компетенцію.

Abstract. The article deals with the means of expressing cross-cultural communication on translation. The types and definitions of translation are given, the components of communicative competence are described and the ways of proper rendering of cross-cultural communication in translation are revealed The author comes to the conclusion that the cross-cultural competence of a specialist that knows a foreign language and the main skills of translation is related to his/her communicative competence, adds a crosscultural dimension to it and has some components of its own that are not part of the communicative competence.
Verbal Realization of Cross-Cultural Communication in Translation
Keywords: міжкультурна комунікація; переклад; комунікативна компетенція; перекладацькі трансформації